Electrochemistry of Inorganic Nanocrystalline Electrode Materials for Lithium Batteries. (2003) - Kwon, C. W.; Hwang, S. J.; Delville, M. H.; Labrugère, C.; Murugan, A. Vadivel; Kale, B. B.; Vijayamohanan, K.; Campet, G.
Abstract : Traditional electrode materials are based on the redox potential difference of the electrode in the course of intercalation/deintercalation reactions. They are generally well-crystalline host compounds either with layered structure such as LiCoO 2 and LiNiO 2, or with tunnel structure like LiMn 2 O 4 Nanocrystalline materials are, however, being re-evaluated recently as 'nanoscience' advances. The electrochemistry of this kind of materials is much different from that of traditional crystalline ones because of their significant 'surface effects'. In connection with that, the nanocrystalline cathode materials are reported to have an enhanced electrochemical activity when the first significative electrochemical step is insertion of Li ions (discharge process). The "electrochemical grafting" concept will be given as a plausible explanation. As illustrative examples, electrochemical behaviors of nanocrystalline manganese oxydes are presented.